Komunikasi Interpersonal Kepala Sma Negeri 1 Geyer Grobogan - Sunarko, Fendy Dwi, Prof. Dr. Sutama, M. Pd (2017)
ABSTRACT This study has three objectives. 1). Describe interpersonal communication on the head of SMA Negeri 1 Geyer Grobogan. 2). Describe interpersonal communication horizontally from the principal. 3). Describe interpersonal communication down of principal. This type of research is a qualitative ethnographic research design. The technique of collecting data through interviews, observations, and documents. Data were analyzed using interactive data analysis. Result: 1). Interpersonal communication on the head of SMA Negeri 1 Geyer Grobogan to the department of education Grobogan done proactively and directly to the written report and feedback on the program of the school. 2). Interpersonal communication horizontally head of SMA Negeri 1 Geyer Grobogan to fellow high school principals do proactively direct telecommunication media and with the principle of equality to establish kekraban, foster brotherhood among school leaders and get educational innovation. 3). Interpersonal communication down from the head of SMA Negeri 1 Geyer Grobogan namely teachers, employees and students are pro-active, dialogue, empathy, warm and open conducted in official / formal and non-formal basis. Keywords: communication interpersonal, principal